Development and evaluation of reverse transcriptase loop-mediated isothermal amplification (RT-LAMP) for avian influenza A and rabies and other lyssaviruses - Markotter, Wanda (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.